An Exceptionally Stable and Water‐Resistant Metal–Organic Framework with Hydrophobic Nanospaces for Extracting Aromatic Pollutants from Water. Issue 38 (31st July 2014) - Wang, Jun‐Hao; Li, Mian; Li, Dan
Abstract A novel hydrophobic metal–organic framework (MOF), namely Cu2L (L=3, 3′, 5, 5′‐tetraethyl‐4, 4′‐bipyrazolate), is synthesized through a stepwise method, and exhibits an unprecedented 3, 4‐c net. The exceptionally thermal, chemical, and air stability of this MOF, especially in water and under acidic or basic conditions, and its selective and fast sorption capacity for hydrocarbons over water warrant its direct use for efficient removal of trace organic wastes (e.g. benzene, toluene, xylene, and mixtures thereof) from contaminated water.